Children's chances : how countries can move from surviving to thriving - Heymann, Jody, 1959- (Harvard University Press, 2013)
Children's Chances urges a shift from focusing on survival to targeting children's full and healthy development. Drawing on comparative data on policies in 190 countries designed to combat poverty, discrimination, child labor, illiteracy, and child marriage, Heymann and McNeill tell what works to ensure equal opportunities for all children.